Assessment of Environmental Cockroach Allergen Exposure - Chew, Ginger L. (Curr Allergy Asthma Rep, 2012)
In the past, cockroach allergen exposure assessment mainly focused on settled dust in homes in low-income urban cities in the United States. That choice was not wrong; without measureable levels of cockroach allergen, it is difficult to show associations with any home characteristics much less with health outcomes (e.g., allergy, asthma). However, recent studies in other suburban areas, schools, and other countries have elucidated the importance of cockroach allergen in these environments too. In addition, characterizing the underlying factors that give rise to cockroach allergen exposure (or protect against it) can lead to more targeted public health interventions. This review discusses different approaches to sampling indoor environments, interprets recent asthma and allergy studies, compares cockroach allergen levels from past studies with those of recent studies, and describes strategies to decrease exposures.